1992
DOI: 10.1152/jappl.1992.73.4.1238
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen replacement in middle-aged women: thermoregulatory responses to exercise in the heat

Abstract: Thermoregulatory, cardiovascular, and body fluid responses during exercise in the heat were tested in five middle-aged (48 +/- 2 yr) women before and after 14-23 days of estrogen replacement therapy (ERT). The heat and exercise challenge consisted of a 40-min rest period followed by semirecumbent cycle exercise (approximately 40% maximal O2 uptake) for 60 min. At rest, the ambient temperature was elevated from a thermoneutral (dry bulb temperature 25 degrees C; wet bulb temperature 17.5 degrees C) to a warm hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 0 publications
9
72
2
Order By: Relevance
“…smaller effect on indices of water and electrolyte metabolism that we observed in response to tamoxifen, compared with those reported in oestrogen-treated women [9,11,12]. It remains to be seen whether the newly-developed anti-oestrogenic agents exhibit similar effects to those of tamoxifen, since the agents within this class of drugs appear to exhibit varying degrees of oestrogenicity at different target tissues.…”
Section: Discussioncontrasting
confidence: 54%
“…smaller effect on indices of water and electrolyte metabolism that we observed in response to tamoxifen, compared with those reported in oestrogen-treated women [9,11,12]. It remains to be seen whether the newly-developed anti-oestrogenic agents exhibit similar effects to those of tamoxifen, since the agents within this class of drugs appear to exhibit varying degrees of oestrogenicity at different target tissues.…”
Section: Discussioncontrasting
confidence: 54%
“…Estrogen-mediated increases in plasma volume are consistent with earlier findings in postmenopausal (2,88) and young women (9,34). The estrogenmediated plasma volume expansion is not always accompanied by changes in water retention, and the mid-luteal phase plasma volume contraction not always associated with greater urine loss.…”
Section: Osmotic Regulation Of Avp and Fluid Balancesupporting
confidence: 89%
“…Sex hormone administration is accompanied by significant water and sodium retention (2, 9), which leads to plasma volume expansion (6, 8,106, 115). In fact, variations in plasma volume at rest and during exercise that are observed following estrogen administration and during different phases of the menstrual cycle are comparable to the reported effects of posture, skin temperature and exercise intensity (43).…”
Section: Protocol A: Sex Hormone Effects On Body Water Regulation Durmentioning
confidence: 99%
“…Therefore, many factors could potentially play a role in the E 2 reduction of T CORE in a supraneutral T AMBIENT . Although the mechanism remains to be determined, these findings are relevant to understanding thermoregulatory dysfunction in menopausal women, who tolerate heat stress better after estrogen replacement therapy (52). We have previously shown that KNDy neurons are required for the rise in LH secretion after the removal of E 2 negative feedback (11).…”
Section: Discussionmentioning
confidence: 95%